2017
DOI: 10.1111/1471-0307.12434
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physicochemical, microstructural and rheological properties of traditional Kope cheese during ripening

Abstract: The effect of ripening time on the microstructural, physicochemical and rheological characteristics of traditional Kope cheese ripened in clay pots was investigated. The moisture content, pH and total nitrogen (TN)/dry matter (DM) of the cheese decreased, and DM, fat in DM and water‐soluble nitrogen/TN increased during this period. Storage and loss moduli increased, while loss tangent decreased; as a result, the elasticity characteristics were greater than the viscous characteristics of the samples. Microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Although data indicates moisture loss during the experiment, which is consistent with most literature findings [44], no statistical significance could be associated to the trends of moisture decrease (the fratio value is 0.76808; the p-value is 0.476501), unlike other sources which communicated p values < 0.05 for moisture decrease findings [55]. Moreover, most authors report lower moisture values for similar type cheeses throughout processing and ripening [46].…”
Section: Sensory Evaluation Of the Food Matrix Samplessupporting
confidence: 81%
“…Although data indicates moisture loss during the experiment, which is consistent with most literature findings [44], no statistical significance could be associated to the trends of moisture decrease (the fratio value is 0.76808; the p-value is 0.476501), unlike other sources which communicated p values < 0.05 for moisture decrease findings [55]. Moreover, most authors report lower moisture values for similar type cheeses throughout processing and ripening [46].…”
Section: Sensory Evaluation Of the Food Matrix Samplessupporting
confidence: 81%
“…As expected, the RD and RI values increased ( p < 0.05) during ripening, which is required to promote the proteolysis process. In comparison to the similar traditional types of cheeses, the RI and RD values were somewhat different: higher than those reported for Xinotyri cheese, made from raw goat's milk without starter culture and ripened for 180 days (Bontinis et al., 2012), higher than Kope cheese, made from sheep's milk and ripened for 90 days (Hasanzadeh et al., 2018), while lower than that reported for Tulum cheeses, made with cloth, stomach, animal skin, pot, and plastic package materials (Tarakçı & Durmuş, 2016; Tekin & Güler, 2019) and also lower than Possti cheese, made from raw sheep's milk, without starter culture and filled into sheepskins and ripened in a human‐made cave for 90 days (Hemmatian et al., 2015). These differences may be attributed to the high salt content in moisture (S/M) of our Kope cheese sample.…”
Section: Resultsmentioning
confidence: 63%
“…Since this preparation stage may take one or two months, the salt content of curd may affect the quality of the final product. A few research have previously reported on Kope cheese and its properties including the histamine content (Ehsani et al., 2012), effects of pasteurization and packaging on its physicochemical and sensory properties (Sarbazi et al., 2015), and the influence of ripening time on the structural, rheological, and physicochemical properties of Kope cheese (Hasanzadeh et al., 2018). Cheese ripening is a complex and dynamic biochemical process including primarily lipolysis, proteolysis, lactate metabolism, followed by secondary events, leading to the development of volatile compounds (VCs) and gross composition, which makes an important contribution to flavor perception and texture properties of cheese (Kalit et al., 2020).…”
Section: Introductionmentioning
confidence: 99%